Measuring the effect of subprime lending on neighborhood foreclosures: evidence from Chicago - Immergluck, Dan; Smith, Geoff (2005)
Since the early 1990s, there has been a very large growth in mortgages made by so-called subprime lenders, which specialize in lending to borrowers with credit history problems. One reason for concern about this trend is that it has been associated with a large and simultaneous rise in forcelosures, which can entail significant costs not just for those directly affected but also for surrounding neighborhoods and larger communities. This study uses multivariate estimations to quantify the impact of subprime lending on neighborhood foreclosure levels. After controlling for neighborhood demographics and economic conditions, the authors find that subprime loans lead to foreclosures at far greater rates than do prime loans. Moreover, subprime lending appears to account for a substantial share of foreclosure activity in high-foreclosure neighborhoods. - Reproduced.
Keywords: Mortgage; Loans